Improving the functioning of the rural financial markets of Armenia - Milada Kasarjyan (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Theoretical literature suggests that social capital, respectively the underlying social networks, facilitate access to otherwise lacking production factors such as financial resources. In addition, the manifestation of different dimensions of social capital is suggested to facilitate collective action and better outcomes in communities. This work analyses by means of Social Network Analysis the role of social capital (bonding and bridging dimensions) in accessing productive resources, in particular access to information and micro-credit. In addition, it determines empirically the significance of social capital (structural and cognitive dimensions) for the credit repayment performance of joint liability borrowing group members. The significance of both cognitive and structural social capital shows that it is essential to consider different dimensions of social capital in such an analysis. Otherwise, analysis may result to biased results. The results suggest that transition brought not only socio-economic changes but also changes of social structures and social support networks to rural Armenia. Though village culture appears to be preserved, social support networks prioritise and benefit the kin members first. – – Die theoretische Literatur zeigt, dass Sozialkapital bzw. soziale Netzwerke den Zugang zu ansonsten fehlenden Produktionsfaktoren wie finanzielle Ressourcen erleichtern. Darüber hinaus wird davon ausgegangen, dass das Vorhandensein von individuellem Sozialkapital kollektives Handeln und bessere Ergebnisse in den Gemeinden erleichtert. Die vorliegende Arbeit analysiert mit Hilfe der Social Network Analysis die Rolle des Sozialkapitals beim Zugang zu Produktionsressourcen, insbesondere den Zugang zu Informationen und Mikrokrediten. Darüber hinaus bestimmt sie empirisch die Bedeutung von Sozialkapital für die Rückzahlungsleistungen von einzelnen Mitgliedern im System der gemeinschulderischen Kreditgruppen. Die Bedeutung sowohl der kognitiven als auch der strukturellen Sozialkapitalindikatoren zeigt, dass es wichtig ist, verschiedene Formen von Sozialkapital in einer solchen Analyse zu betrachten. Die Betrachtung nur eines Typs, des strukturellen oder kognitiven unter Ausschluss des anderen, kann zu überbewerteten und verzerrten Ergebnissen führen. Die Ergebnisse lassen darauf schließen, dass die Transformation nicht nur sozioökonomische Veränderungen, sondern auch Veränderungen in den sozialen Strukturen und sozialen Netzwerken zur Unterstützung des ländlichen Raumes Armeniens gebracht hat. Obwohl die Dorfkultur bewahrt geblieben scheint, bieten soziale Netzwerke zuerst deren Mitgliedern Vorrang und Vergünstigungen.
urn:nbn:de:gbv:3:2-18724
Keywords: 330